2017
DOI: 10.7150/jca.16723
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral CRISPR/Cas9 vector mediated miR-21 gene editing inhibits the epithelial to mesenchymal transition in ovarian cancer cells

Abstract: CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats) mediated genome editing is a powerful approach for loss of function studies. Here we report that lentiviral CRISPR/Cas9 vectors are highly efficient in introducing mutations in the precursor miRNA sequence, thus leading to the loss of miRNA expression and function. We constructed four different lentiviral CRISPR/Cas9 vectors that target different regions of the precursor miR-21 sequence and found that these lentiviral CRISPR/Cas9 miR-21 gR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 23 publications
0
75
0
1
Order By: Relevance
“…Next, we performed a Matrigel invasion assay. JHOS‐2 was less invasive compared with SKOV3 and NIH‐OVCAR3, which showed intrinsic invasive ability . Cell invasion was significantly increased by ZNF671 depletion in the SKOV3 and NIH‐OVCAR3 cell line, whereas ZNF671 depletion had a minimal effect on cell invasion by JHOS‐2 (Figure and Figure ).…”
Section: Resultsmentioning
confidence: 88%
“…Next, we performed a Matrigel invasion assay. JHOS‐2 was less invasive compared with SKOV3 and NIH‐OVCAR3, which showed intrinsic invasive ability . Cell invasion was significantly increased by ZNF671 depletion in the SKOV3 and NIH‐OVCAR3 cell line, whereas ZNF671 depletion had a minimal effect on cell invasion by JHOS‐2 (Figure and Figure ).…”
Section: Resultsmentioning
confidence: 88%
“…Cell proliferation was calculated using the ratio of BrdU positive cells to cell nuclei stained with propidium-iodide (PI) or DAPI. Cell proliferation was also examined with MTT assay as we published previously [30]. …”
Section: Methodsmentioning
confidence: 99%
“…A scratch was created using a sterile 20 ÎŒl pipette-tip and washed 3 times with PBS. Fresh growth medium was added for additional 24 h. Migration rate was calculated using to (area of the wound area at 0 h− the wound area at 24 h)/the wound area at 0 h. Cell migration was also examined using trans well plates as we published previously [30]. …”
Section: Methodsmentioning
confidence: 99%
“…Using this method, they successfully disrupted the expression of miR-21 and found that disruption of pre-miR-21 sequences results in decreased cell proliferation, migration and invasion in ovarian cancer cells. 45 Except for editing/regulating these miRNAs discussed above, CRISPR/Cas9 has also shown vast applications toward other miRNAs, like, miR-137, miR-93, miR-309, miR-126a/b etc., in various cancer cells or organisms. [46][47][48][49][50][51][52] CRISPR/Cas9 for lncRNA editing in cancer In addition to miRNAs, lncRNAs have been reported to be successfully edited/regulated by CRISPR/Cas9 system.…”
Section: Crispr/cas9 For Mirna Editing In Cancermentioning
confidence: 99%